Role of Rotational Kinematics in Minimizing Elbow Varus Torques for Professional Versus High School Pitchers - Luera, Micheal J. (Orthop J Sports Med, 2018)
BACKGROUND: Elbow injury rates among baseball pitchers are rapidly rising. However, this increase has been most dramatic among high school (HS) pitchers. PURPOSE: To examine pitch velocity and the kinetic and kinematic characteristics of HS versus professional (PRO) pitchers to identify potential differences that may play a role in the increased risk of ulnar collateral ligament injury in youth pitchers. STUDY DESIGN: Controlled laboratory study. METHODS: A total of 37 HS (mean ± SD: age, 16 ± 1 years) and 40 PRO (age, 21 ± 2 years) baseball pitchers completed maximal-effort baseball pitches during a single testing session, from which pitch velocity (PV), absolute and normalized elbow varus torque (EVT(A) and EVT(N), respectively) during arm cocking and at maximum shoulder external rotation (MER), and 8 other elbow and shoulder torques or forces and rotational kinematics of the pelvis and trunk were analyzed, recorded, and compared. RESULTS: PV was greater in PRO than HS athletes; EVT(A) was greater in PRO than HS athletes during arm cocking and at MER; but EVT(N) was similar during arm cocking and greater in HS than PRO athletes at MER. In PRO athletes, PV was not related to EVT(A) during arm cocking or MER (r = 0.01-0.05). Furthermore, in PRO athletes, EVT(A) during arm cocking and at MER were inversely related to upper trunk rotation at hand separation and foot contact and to pelvis rotation at elbow extension (r = –0.30 to –0.33). In contrast, in HS athletes, PV was strongly related to EVT(A) during arm cocking and MER (r = 0.76-0.77). Furthermore, in HS athletes, PV and EVT(A) during arm cocking and at MER were moderately or strongly related to the other elbow and shoulder torques and forces (r = 0.424-0.991), and EVT(A) was not related to upper trunk rotation or pelvis rotation throughout the throwing motion (r = –0.16 to 0.15). CONCLUSION: The kinetic and rotational kinematic differences observed between PRO and HS pitchers in this study may help explain the greater performance of PRO pitchers while allowing them to minimize EVT during pitching. HS pitchers, however, do not appear to be as capable of utilizing the forces generated by rotation of their trunk and pelvis to aid in pitching, and those who throw the hardest generate the greatest forces at the shoulder and elbow. As a result, they experience higher EVTs relative to their body size, which may place them at an increased risk of injury. CLINICAL RELEVANCE: HS pitchers throw harder primarily by generating larger forces in the arm and shoulder. Thus, owing to the relative physical immaturity of HS versus PRO pitchers, these factors may place them at an increased risk of injury. Coaches may first wish to focus on improving the rotational kinematics of HS pitchers rather than first focusing on achieving greater pitch velocities.